Assessment of the evaluation approaches of agricultural projects in Bojanala Region of the North West Province, South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2010.